The impacts of stator outside diameters on induction motor nameplates: Analysis by using a finite element - Ismail, Daut, Prof. Dr.; Mastika, Abdullah; Gomesh Nair, Shasidharan; Yanawati, Yahya; Nor Shafiqin, Shariffuddin; Pungut, Ibrahim (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/